ANALYSIS OF BEHAVIORS OF SIDODADI MARKET TRADERS BASED ON TAFSĪR AL-JᾹMI' LI AḤKᾹM AL-QUR'ᾹN IMAM AL-QURṬUBĪ ABOUT CHARACTERISTICS OF MADYAN TRADERS - Nirwana, Andri; Tamami, Riza; Hidayat, Syamsul; Akhyar, Sayed (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
The behavior of the Madyan people mentioned in the Qur'an reflects inappropriate behavior in trading. Imam al-Qurṭubī in his tafsir, al-Jāmī' li Aḥkām al-Qur'ān, mentioned that three things they did were mentioning untrue prices, hiding product defects, and cheating in weighing and measuring. This paper aims to analyze these three behaviors of traders at the Sidodadi market, Kleco. Through the interview method, there are three points that are able to be concluded. First, as many as 66% of Kleco market traders always explain the aspects of goods defects. Second, there are 68% of them consistently provide the same price to buyers. Third, there are 88% of them do not cheat in scales and measures. In general, it can be understood that the majority of Kleco market traders do not have trading behavior like the Madyan people